SISTEM TOKO ONLINE RIZALSHOP BERBASIS WEBSITE - cahyadi, hagni (Jurnal Teknologi dan Bisnis, 2021)
The times and technology of Internet usage in Indonesia and the world at large continues to grow. In fact it's a lifestyle most of the world's population. Along with the continued increase in the user's internet service, the cheaper and easier to get internet service. Online shopping activity is growing rapidly and is popular in many circles. Moreover, fashion products such as clothes and accessories, all available in trending website and can be accessed easily. Online Shop countless easy to run, because it does not require a large capital. Enough with the pictures of the products and internet access to market, this business has been able to walk. Online Shop has several advantages such as easy and cheap to access, because the customer is enough to see a sample of goods over the internet, without having to come to a store such as buying and selling in general. It is therefore not surprising that very fast growing Online Shop. Online stores can be accessed anytime 24 hours. On appeal to the store - a store that only operates during office hours. Coupled with a well needed energy in order to achieve the desired store. For online shopping right now - really have more value in the eyes of consumers to shop. It is expected that by using the web-based information systems, people can access information and be able to shop with ease, fast, and efficient, and can be done whenever and wherever they are, regardless of distance and time.